Relative Age Effects in Basketball: Exploring the Selection into and Successful Transition Out of a National Talent Pathway - Adam L. Kelly; Sergio Lorenzo Jiménez Sáiz; Alberto Lorenzo Calvo; Alfonso de la Rubia; Daniel T. Jackson; Mark A. Jeffreys; Charlie Ford; Dave Owen; Sara Diana Leal dos Santos (MDPI AG, 2021)
Relative age effects (RAEs) appear consistently prevalent throughout the youth basketball literature. However, the selection into and successful transition out of a national talent pathway in basketball is yet to be explored. Thus, the primary aim of this study was to explore the influence of relative age, gender, and playing time based on the selection into the Regional Talent Hubs and Basketball England youth teams (U16, U18, and U20) and the successful transition into the England National Senior Teams. Participants who were selected into the male (n = 450) and female (n = 314) Basketball England Talent Pathway were allocated into one of three cohorts: (a) Regional Talent Hubs (U12 to U15; n = 183), (b) England National Youth Teams (U16, U18, and U20; n = 537), and (c) England National Senior Teams (n = 44). A chi-square test was used to compare the birth quarter (BQ) distributions of each cohort against the expected distributions, with a Cramer's V (Vc) used to interpret effect sizes. Odds ratios (OR) and 95% confidence intervals were also calculated to compare the likelihood of each BQ being represented. Males revealed significant RAEs across both the Regional Talent Hubs (p < 0.001, Vc > 0.29, OR = 10) and England National Youth Teams (p < 0.001, Vc > 0.17, OR = 3.1). In comparison, females only had significant RAEs in the Regional Talent Hubs (p < 0.001, Vc > 0.29, OR = 2.3). Despite RAEs being prevalent throughout youth levels, there were no significant differences in the BQ distribution based on playing time and those who made the successful transition to the England National Senior Teams. These findings demonstrate the potential mechanisms of RAEs in basketball, as well as the impetus to explore more equitable competition structures within the England Basketball Talent Pathway.